Dynamic Mechanical Analysis of Waste Polyethylene Terephthalate Bottle - Misri, Zainora; Wan Ibrahim, Mohd Haziman; Abdullah, Abd Halid; A.S.M, Awal; Shahidan, Shahiron; Sheikh Khalid, Faisal; Arshad, Mohd Fadzil; Putra Jaya, Ramadhansyah (International Journal of Integrated Engineering, 2019)
Polyethylene terephthalate (PET) led to the disposing and managing issue due to it extensively consumptions. Hence, its application in construction field particular on concrete production has become general. However, the preliminary study on PET itself is very limited. This study was focused on the investigation on mechanical properties of PET film using dynamic mechanical analysis (DMA) over a temperature range of 40-180Â°C at fixed frequency of 1 Hz. In the paper, glass transition temperature were analyzed with the curves of storage modulus (Eâ€™), loss modulus (Eâ€) and tan delta. The results show decreasing curve of storage modulus, meanwhile loss storage and tan delta present same curve which is increases with temperature as glassy phase and radically decreases due to rubbery phase. From these curves, the glass transition temperature (Tg) of PET have been characterized which the value has been found to be 114Â°C. Generally, this study could provide better characterization of a material in order to examine the ability of a material to store or lose energy.